2016
DOI: 10.1016/j.heliyon.2016.e00207
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development and optimization of Lamivudine 300 mg and Tenofovir Disoproxil Fumarate (TDF) 300 mg FDC tablets by D-optimal mixture design

Abstract: The usage of fixed dose combination (FDC) tablets of Lamivudine and Tenofovir Disoproxil Fumarate (TDF) is increasing due to increased incidences of HIV/Hepatitis B and HIV/TB co-infections. This is likely to increase the financial crisis due to limited resources for funding procurement of ready-made products from the pharmaceuticals manufacturing leading countries. Therefore, production of local oral tablets containing Lamivudine and TDF FDC is inevitable. Lamivudine 300 mg/TDF 300 mg tablets were developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…DCPA is a nonhygroscopic filler and absorbed less than 1 % water [17], therefore, when % DCPA in filler (X1) increased, the water penetration into the tablet may be slowed down and hence, the disintegration process was prolonged. This was in line with the rule reported previously by Tibalinda P [18].…”
Section: Effect Of Variables On Disintegration Timesupporting
confidence: 94%
“…DCPA is a nonhygroscopic filler and absorbed less than 1 % water [17], therefore, when % DCPA in filler (X1) increased, the water penetration into the tablet may be slowed down and hence, the disintegration process was prolonged. This was in line with the rule reported previously by Tibalinda P [18].…”
Section: Effect Of Variables On Disintegration Timesupporting
confidence: 94%
“…Response surface methodologies, such as mixture designs, have recently been used in the formulation of microemulsions (ME) [ 25 , 26 , 27 ], self-emulsifying drug delivery systems (SEDDS) [ 28 , 29 , 30 ], liposomes [ 31 , 32 ] and tablets [ 19 , 33 , 34 , 35 , 36 , 37 , 38 ]. The D-optimal design is one of the most used methodologies in this field, because it allows different composition constraints, in which the sum of all components is constant (100% w / w ).…”
Section: Introductionmentioning
confidence: 99%
“…These results, therefore, suggest that both tenofovir and lamivudine can induce an inflammatory cascade in the brain, which drives neurodegeneration as seen in HAND (Rojo et al 2008;Gelders et al 2018). It is possible that in these conditions, reactive astrocytes or microglia may instigate the production of pro-inflammatory proteins associated with the onset of various neurodegenerative diseases (Lu et al 2010;Vivithanaporn et al 2016), including AIDS-induced parkinsonism (Devine et al 2018). Our results agree with findings from a previous investigation that showed that administration of efavirenz increased astrogliosis in mice (Petrov et al 2019).…”
Section: Discussionmentioning
confidence: 99%